Analisis Kebutuhan Media Pembelajaran E-Modul dalam Pembelajaran Tematik Siswa Kelas 5 Sekolah Dasar - Bima Priyamoko; Dewi Indrapangastuti (Universitas Sebelas Maret, 2025)
E-module media is a type of learning tool that facilitates students’ understanding of subject matter within thematic learning by presenting content in a comprehensive format. This study aims to analyze the extent to which fifth-grade elementary school students require thematic e-module learning media. The research utilized a descriptive quantitative method, with data collected through the distribution of closed-ended questionnaires to fifth-grade students as research participants. The data were analyzed by calculating the percentage of responses. The analysis of learning media needs involved three aspects: students’ learning styles and interests, prior experience using media, and the perceived need for such media. The results indicated that the need for e-module media among fifth-grade elementary students reached 83.33%, placing it in the category of “mostly needed.” Students reported favorable experiences and interest in using digital media and expressed a high level of need for e-modules in thematic learning settings. Media E-Modul merupakan salah satu media yang dapat memudahkan siswa dalam memahami materi Pelajaran dengan muatan tematik karena mampu menyampaikan materi secara utuh. Penelitian ini bertujuan untuk menganalisis apakah siswa kelas V sekolah dasar membutuhkan terhadap media pembelajaran E-modul tematik. Pada Penelitian ini menggunakan metode deskriptif kuantitatif dengan teknik pengumpulan data melaui penyebaran angket tertutup kepada siswa kelas V Sekolah Dasar sebagai subjek penelitian. Teknik analisis data dengan cara mempersentasekan data yang diperoleh. Aspek yang dimuat dalam menganalisis kebutuhan terhadap sebuah media mencakup aspek minat dan gaya belajar siswa, pengalaman dalam menggunakan media, kebutuhan siswa akan media. Hasil penelitian menunjukkan bahwa kebutuhan akan media pembelajaran e-modul pada siswa kelas V sekolah dasar memiliki presentase 83,33% termasuk kategori Sebagian besar membutuhkan. Siswa memiliki pengalaman dan minat belajar yang baik terhadap media digital serta menunjukkan kebutuhan tinggi terhadap penggunaan e-modul dalam pembelajaran tematik.